Effectiveness and Safety of Primary Thromboprophylaxis in Children with Cancer: A Systematic Review of the Literature and Network Meta-Analysis - Pelland-Marcotte, Marie-Claude; Tole, Soumitra; Pechlivanoglou, Petros; Brandão, Leonardo Rodrigues (Thrombosis and Haemostasis, 2019)
Thromboembolism (TE) is a well-recognized complication of pediatric cancer and can lead to mortality and excess morbidity. There is conflicting evidence about the effectiveness and safety of thromboprophylaxis in children. We conducted a systematic literature review and network meta-analysis of primary pharmacological thromboprophylaxis in children and adolescents (0–21 years) with cancer. The primary outcomes were objectively proven TE and major bleeding. The network meta-analysis included comparisons of multiple alternatives simultaneously: antithrombin (AT) replacement, low molecular weight heparin (LMWH), vitamin K antagonists (VKAs), and standard of care (SOC) defined as no thromboprophylaxis or low-dose heparin for catheter patency. Six articles describing 1,318 patients were included (mean age: 6.7 years, 56.7% male). Acute lymphoblastic leukemia was the underlying diagnosis in 97.5% of patients. All studies were considered at moderate or high risk of bias. LMWH was the only agent associated with lower odds of TE compared with SOC (odds ratio [OR]: 0.23, 95% confidence interval [CI]: 0.06–0.81). No statistically significant difference was detected between other thromboprophylaxis modalities and SOC. Tau2 and I2 suggested a high degree of heterogeneity. No statistically significant differences in the odds of major bleeding were found between AT replacement, LMWH, VKA, and SOC. Current evidence suggests that low-dose LMWH is effective and safe to prevent TE in children with cancer but is insufficient to conclude if AT replacement or VKA are effective thromboprophylaxis options. Further research, notably randomized controlled trials enrolling children with diverse types of cancer, is crucially needed.
Keywords: thrombosis; cancer; thromboprophylaxis; children